STRENGTHENING THE FOUNDATIONS OF BELT FOR RECONSTRUCTION OF THE FIRST FLOOR (Municipal economy of cities. Series: «Economy science», 2013)
The variants gain strip foundations of buildings in the reconstruction of the first floor with an increase in their doorways, and proposes a methodology for calculating these gains.